OBTENÇÃO, CARACTERIZAÇÃO E AVALIAÇÃO DA ATIVIDADE ANTIOXIDANTE E CITOTÓXICA DE NANOPARTÍCULAS DE POLI (ÁCIDO LÁCTICO) CONTENDO ÁCIDO URSÓLICO - ANTÔNIO, EMILLI (2016)
Ursolic acid (UA) is a pentacyclic triterpenoid present in many food and medicinal species, which was consecrated due to its antioxidant action, and currently has expanded its research due to its ability to inhibit various stages in the development of tumors. However, its clinical application is limited due to its low aqueous solubility, which results in low oral bioavailability, restricting its effectiveness. In an attempt to overcome these limitations, the present work developed nanoparticles of poly (lactic acid) (PLA) containing UA through the method of emulsification-solvent evaporation. In order to obtain a tool able to quantify the UA present in nanoparticles, an analytical method using high-performance liquid chromatography (HPLC) coupled to a photodiode detector array (PDA) was developed and validated in accordance with current norms. PLA nanoparticles containing UA were successfully obtained and presented an encapsulation efficiency of 96%, and 246 nm in mean size, with spherical or slightly oval morphology. Zeta potential of the formulation was -24,6 mV, a value which ensures a good physicochemical stability. The spectroscopic in infrared, X-ray diffraction, differential scanning calorimetry and thermogravimetric analysis suggests interaction/complexation of UA with the polymeric matrix and amorphization of the drug promoted by nanoencapsulation process. Stability study showed that the best condition for storage of NP's was at room temperature, since in this condition all parameters were stable for 6 months. The in vitro release study showed that UA was released from the polymeric matrix over two constants (α, β), suggesting a second order kinetics. At the end of 120 h about 60% of the encapsulated UA was released by diffusion. In cytotoxicity test front red blood cells, it was observed that the NP's containing UA showed less toxicity on cells than free drug. When evaluated the cytotoxicity over tumor cells line B16 -F10, UA nanoencapsulated keeped the antitumor capacity of the drug. By studying the antioxidant activity via inhibition of hypochlorous acid, it was observed that the nanoencapsulation process does not influence the UA antioxidant capacity, whereas after 72 h, the NP's presented inhibition capacity similar to free UA. Thus, it is concluded that NP's containing UA developed in this study had adequate physic chemical characteristics, which make them potential drug delivery systems while maintaining the antioxidant and antitumor activity of the UA and decreasing its cytotoxicity on normal cells.